The influence of low suberythemal doses of ultraviolet-B radiation on methylenetetrahydrofolate reductase expression in the skin - Lesiak, Aleksandra; Wódz-Naskiewicz, Karolina; Pawliczak, Rafał; Rogowski-Tylman, Michał; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Ultraviolet radiation (UVR) is one of the major factors involved in skin photocarcinogenesis. Although it is well known that UVA can destroy foliate, the effect of UVB on foliate status is still not clear. Some data indicate that foliates, especially their metabolite 5-methyltetrahydrofolate, can protect DNA against UV-induced strand breaks. Methylenetetrahydrofolate reductase (MTHFR) plays an essential role in the foliate metabolic pathway. Objective . To assess the expression of MTHFR in UVB exposed skin. Material and methods . The study consisted of 4 groups of healthy individuals who were whole-body UVB irradiated for 10 days with 0.7 MED on each occasion, or whole-body irradiated as before followed by a single high dose of UVB (10 × 10 cm), or were irradiated only with a single dose of UVB (3 MED) on a small area of the body, or were not irradiated. Skin biopsies were taken from all participants and MTHFR expression was assessed (Western blot). Results . MTHFR expression was significantly higher in the volunteers who were whole-body irradiated for 10 days compared to the subjects who were whole-body irradiated for 10 days followed by a single 3 MED UVB dose (p < 0.05). Conclusion . The enhanced expression of MTHFR in human skin under repeated low doses of UVB might be evidence of the photoprotective properties of foliates.